2013
DOI: 10.1890/12-1025.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for an ideal free distribution in a breeding population of a territorial songbird

Abstract: Abstract. According to the ideal despotic distribution (IDD), dominant individuals gain a fitness advantage by acquiring territories that are of higher quality, thereby forcing other individuals into lower quality habitat. In contrast, the ideal free distribution (IFD) predicts that local density is a function of habitat quality, but that individuals achieve the same fitness in different habitat types as a result of density-dependent variation in territory size. Although the IFD represents an alternative, popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 68 publications
4
37
0
Order By: Relevance
“…Setting aside areas with high densities is assumed to have the greatest long-term potential to stop the decline of species that are limited by the amount of breeding habitat remaining. High density areas also tend to have the highest per unit area reproductive output (Skagen and Yackel Adams 2010; Haché et al 2013). Thus, identifying areas with high density and producing the greatest among of young, is key to defining critical habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Setting aside areas with high densities is assumed to have the greatest long-term potential to stop the decline of species that are limited by the amount of breeding habitat remaining. High density areas also tend to have the highest per unit area reproductive output (Skagen and Yackel Adams 2010; Haché et al 2013). Thus, identifying areas with high density and producing the greatest among of young, is key to defining critical habitat.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was no evidence for local extinction or a dramatic decline in mature forest associates. In the same study plots, Haché et al (2013) found no effect of selection harvesting on per capita productivity and daily nest survival rate of Ovenbirds, suggesting that individuals can nest successfully in selection cut stands (see also Leblanc et al 2011) by increasing the size of their territories to account for lower food abundance. There is also growing evidence that early-seral stands can be important for mature forest associates during the postfledging period (Vitz andRodewald 2006, Chandler et al 2012).…”
Section: Discussionmentioning
confidence: 78%
“…The Ideal Free Distribution assumes individuals are free to choose any habitat, have perfect knowledge of habitat suitability and of the distribution of competitors, and are equal competitors (Fretwell & Lucas, ). Despite its unrealistic assumptions (Kennedy & Gray, ), the Ideal Free Distribution and its extensions have been useful for predicting the spatial distribution of organisms between habitats (Haché & Bayne, ; Milinski, ; Walhström & Kjellander, ). Another central assumption of habitat selection models, however, is that populations experience density dependence (Clutton‐Brock, Major, Albon, & Guinness, ; Morris, ; Skogland, ).…”
Section: Introductionmentioning
confidence: 99%